Emergency Department Overcrowding and Its Potential Impact on Care Processes: A Literature Review - Yusron Amin; Haswita Haswita (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Emergency department overcrowding was a obstacle of providing timely and effective care in emergency department. This condition had negatively impact on many aspect of care proccess. There were different finding related to impact of emergency department overcrowding in care process. The aim of the study was to analyze research articles that discusses emergency department overcrowding and its potential impact on care proccess. The study was literature review using database journal resources from PubMed, Proquest, and ScienceDirect. Emergency department (ED), Overcrowding, and impact we used as keyword. Inclusion criteria of the study were original article, Published at 10 years later (2012-2022), written in english language, focus on patient, staff, or health care system level. Whereas, the exclusion criteria were overcrowding because of other condition (endemic or infection disease), and not focus on patient, staff, or health care system. 9 selected articles that met inclusion criteria were analysed based on author, years, title, and main idea of the study. The finding of the study were emergency department overcrowding had negatively impact on care process including patients, staff, and healthcare system. Impact on patients including increasing mortality and admission rate, impact on staff including increasing workload and non-adherence for practicing best guidelines, meanwhile impact on healthcare system including innapropriate triage proccess and increasing Length of Stay (LOS). Need an effort to decrease impact of ED overcrowding especially on patient, staff, and healthcare system. The result of the study could be used as considering to formulate an effort to reduce impact of ED overcrowding by controlling patient, staff, and healthcare system factors.